the phenomenon of affliction In pre-Islamic poetry An analytical study (Journal of the College of Basic Education, 2023)
This research deals with an important phenomenon that recorded its great presence in Arabic poetry before Islam, which is the phenomenon of (humiliation), which was linked between two main directions: the social dimension, and the subjective psychological dimension. As the ancient poet crystallized the dimensions of this human expression in the meanings of his poetry, and in addressing society. And because it is a subjective social phenomenon, the research used some sources of psychology to justify its presence and the strength of its interaction in the human expression that the ancient poet tried to be a part of.This phenomenon contained the vocabulary of Arab life with its sensual and moral details, which was richly reflected in the meanings immortalized in poetry in the style of humiliation and blame. The matter in which the research attempted to trace the movement of the phenomenon in the ancient poetic text, and to show its levels within two main topics: - The first topic: The poet is excused.- The second topic: the poet is excused.Some studies and articles examined partial aspects of the phenomenon (such as Al-Aadhilah and Al-Aadhil..), but they did not study the phenomenon with its title and its general movement in ancient poetry. Which moved this research to complete the efforts that preceded it, and to study this phenomenon in its general title, and the paths it produced in its social and personal movement. Therefore, this research was an attempt in this direction.Poetry was and still is a tool of awareness for the Arab poet, through which he was able to express his personal and social potential... and his vision of life around him, as "the creativity process is affected by the interactions of people with others and their relationships with them, as well as the social context in which these people exist" ( ). Just as it is said that language is a social phenomenon, it can be said that poetry is a social creative phenomenon that contained Arab life with its features and spirit... We do not lose sight of Ibn Abbas's statement: "Poetry is the Arabs' office" (). It is the phrase that we understand in this research that poetry is a vision of the world, not just a physical description of it. The poet recreates life with a vision and a new self-reflection that achieves balance and adaptation to the society in which he lives, and balance with himself as well. Thus, poetry turns into a justifying or adaptive behavior in the poet's attitudes towards life and constitutes one of the important defensive means in achieving self-respect and life. Poetry becomes a means of defense for the poet ( defense mechanisms ) in which he restores the achievement of psychological and social balance without falling into conflict (3).